Blackbird, blackbird, what do you do? - McLelland, Kate (London : Hodder Children's Books, 2017)
Pip the blackbird does not know what he wants to do, and visits Heron, Owl, Puffin, and Pigeon on a journey of discovery before he realizes what he loves to do most of all.
Keywords: Children's stories